Mixed convection boundary layer in porous media - Lo, Michael Jun Ke. (2009)
This project is dedicated to find out the characteristic of the mixed convection boundary layer in porous media. This is done by using the Matlab Simulation software to generate out the approximated value for the boundary layer. In order to achieve the solution; studies will have to be made on the type of boundary layer, different kinds of convection heat transfer, interaction of porous media on the boundary fields. With the understanding of the theories and the mathematic formulation, modified equation will be used to justify the similarity solutions of the mixed convection boundary layer in porous media discussed in previous works. The result of the equation shows the solution of the aiding and the opposite flow of the fluid. The opposite flow will have a bifurcation point when it reaches the critical suction parameter. The boundary solution for that will shows dual solutions which mean that the top and bottom profile will converge. This is due to the hot and cold gradient from the wall forcing the fluid to have a similar answer. This could be seen in the figure in result section.